A Series of Unfortunate Events: The Grim Grotto - Book 11 - Snicket, Lemony; Helquist, Brett (New York : HarperCollins, 2004)
Still pursued by the evil Count Olaf, the Baudelaire orphans attempt to reach a very important VFD meeting, but first they must travel in a rattletrap submarine to the Gorgonian Grotto, a dangerous underwater cave, in search of the sugar bowl.
Keywords: Orphans -- Fiction; Brothers and sisters -- Fiction; Submarines (Ships) -- Fiction; Humorous Stories